2014
DOI: 10.1142/s0218810414300046
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Complications and Recurrence Rate of Arthroscopic Resection of Volar Wrist Ganglion

Abstract: (1) level I-V evidence, (2) documentation of the number of wrists subjected to surgery, (3) documentation of surgical techniques used on wrists, and (4) documentation of surgical or post-surgical complications and recurrence rate of a volar wrist ganglion after arthroscopic resection. A complication was defined as an adverse outcome that was directly related to the operative procedure. Between 2001 and 2012, 13 articles met the inclusion criteria. Two articles were excluded and 11 were reviewed. A total of 232… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
2
12
0
1
Order By: Relevance
“…This confirms the results from two systematic reviews that found recurrence following arthroscopic resection in 9% of 587 dorsal ganglion cysts and 6% of 232 volar ganglion cysts. 11,12 We reported a total of three complications in our patient group (6%), which is similar to complication rates described in other studies on arthroscopic ganglion cysts resection, although numbers vary widely (0-56%). 4,12 Noticeably, these rates are lower than those of open resection (4 vs. 14%), according to the meta-analyses by Head and colleagues.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This confirms the results from two systematic reviews that found recurrence following arthroscopic resection in 9% of 587 dorsal ganglion cysts and 6% of 232 volar ganglion cysts. 11,12 We reported a total of three complications in our patient group (6%), which is similar to complication rates described in other studies on arthroscopic ganglion cysts resection, although numbers vary widely (0-56%). 4,12 Noticeably, these rates are lower than those of open resection (4 vs. 14%), according to the meta-analyses by Head and colleagues.…”
Section: Discussionsupporting
confidence: 87%
“…11,12 We reported a total of three complications in our patient group (6%), which is similar to complication rates described in other studies on arthroscopic ganglion cysts resection, although numbers vary widely (0-56%). 4,12 Noticeably, these rates are lower than those of open resection (4 vs. 14%), according to the meta-analyses by Head and colleagues. 4 Similar to this study, complications in other studies include hematoma, infection, neuroma, painful scar tissue, and neuropraxia.…”
Section: Discussionsupporting
confidence: 87%
“…The method of excision may also lower recurrence rates: Head et al reported a 76% reduction in recurrence rate with open surgical resection compared to aspiration, (16) while arthroscopic resection for volar wrist ganglions was described to have a recurrence rate ranging from 0% to 20%. (17) The second most common benign tumour excised in our study was GCTTS, which is also referred to as pigmented villonodular tenosynovitis. Our study suggests that distal to the MCPJs, GCTTSs are more commonly excised than ganglions.…”
Section: Discussionmentioning
confidence: 79%
“…Although surgical excision is the golden standard treatment for ganglion cysts, including open or arthroscopic surgical excision, its surgical trauma, postoperative complications (including unsightly scar) and high cost are the main reasons for patients to refuse surgery [6]. In addition, the recurrence rate of surgical excision varies from 3.8-42% [2,10]. So surgeons still attempt to nd a new treatment for ganglion cysts, with the advantages, including high success rate, low recurrence rate, low cost, safe and less surgery trauma.…”
Section: Introductionmentioning
confidence: 99%